Variability and systematic differences in normal, protan, and deutan color naming - Nagy, Balázs V.; Németh, Zoltán; Samu, Krisztián; Ábrahám, György (Frontiers in Psychology, 2014)
Congenital color vision deficients generally demonstrate difficulties in color naming tasks. In our study we investigated the color naming properties and uncertainties of a relatively large group of red-green color vision deficients using quasi monochromatic stimuli and seven basic color terms. The results show large variability in color naming for the color vision deficient when compared to normal color vision and similar alterations when compared protans to deutans. Statistically significant differences were found in specific wavelength ranges between the tested groups. In general, protans and deutans have shown better color naming ability than expected which suggests the use of non-chromatic visual cues.